PERAN SOSIAL MEDIA TERHADAP DAYA TARIK WISATA “NEPAL VAN JAVA” - Fatimaharani Annisa Septiya Ningrum; M. Nazir Salim (Universitas Merdeka Malang, 2021)
Butuh Hamlet is one of the hamlets in Magelang Regency which last year went viral because of its beautiful natural scenery. “Netizens” call on social media, especially Instagram, the title “Nepal van Java”, because the natural panorama and the terraced houses follow the contours of the land, similar to the landscape in Nepal. The viral impact of the Butuh Hamlet has increased the number of domestic tourists and slowly the hamlet has turned into a new popular tourist location. This study aims to determine the influence of social media on the increase and attractiveness of the “Nepal van Java” tour or Butuh Hamlet. With the survey method via google form and observation, the authors took a random sample of 60 people with certain criteria, including “netizens” owning a smartphone and being active on social media. Data analysis uses quantitative analysis techniques with a descriptive approach. The results of the study show that social media has a major influence on the tourist attraction of visiting “Nepal van Java”. Instagram has become a social media that plays an important role in promoting this destination. In summary, social media can prove to be a means of short-term promotion for tourism as evidenced by the significant jump in visitors in a short time at “Nepal van Java”.